Properties of latex ferrocement in flexure - Ramli, Mahyuddin; Suleiman, Mohd. Zailan (2008)
This paper discusses the durability study of polymer-modified ferrocement in comparison with conventional ferrocement particularly when exposed to severe environmental conditions. The development of strength, deformability and fracture properties were slightly different from conventional ferrocement. Test result indicates a significant improvement in reducing and bridging micro cracks, especially in the prepeak load region. Fracture toughness and deformability increased significantly. However, the post peak behaviour was quite similar to conventional ferrocement.